Penatalaksanaan Fisioterapi Pada Low Back Pain Myogenic Di RST. Dr. Soejono Magelang - Amelia, Giema, Yulisna Mutia Sari, SST., Ft., M.Sc. (GRS) (2016)
Background: Low back pain is pain in the lower lumbar spine L1 until the entire sacrum and surrounding muscles. Physiotherapy as one of the health professionals have a role to minimize the risk of complications of lower back pain is more severe. Physiotherapy techniques used in patients with low back pain vary widely to address problems arising from lower back pain. Essay uses SWD and TENS modalities. The purpose of this study was to determine the image of physiotherapy treatment in patients with low back pain miogenik. The purpose of this research: to find a picture of physiotherapy treatment in patients with low back pain miogenik. In conditions of lower back pain due to miogenik raises an issue that is of pain, range of motion (LGS), the muscle spasms in the muscles paravertebra and problems of functional ability, to overcome problem arising in these conditions modality used is Short Wave Dyathermy (SWD) and TENS. Methods: Primary data that physical examination aims to determine the physical condition of the patient, Interview aim to collect data by means of questions and answers between the therapist with the patient that is anamnesis directly with the patient, can also be carried on the family and other people who know the patient's condition that the bias to the source , Observations aims to determine the patient's progress during treatment. Results: To overcome the above problems, the use modalities such as Short Wave Dyathermy (SWD and TENS. Of these modalities obtained significant results are reduced pain, spasm decreased, increased scope of joint motion and functional activity improvement